2023
DOI: 10.3390/ma16165513
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Self-Compacting Concrete Produced with Optimized Volumes of Calcined Clay and Rice Husk Ash—Emphasis on Rheology, Flowability Retention and Durability

Abstract: The durability of concrete requires a dense microstructure which can be achieved by using self-compacting concrete (SCC). Both calcined clay (CC) and rice husk ash (RHA) are promising supplementary cementitious materials (SCMs) that can partially replace cement, but their use in SCC is critical due to their higher water demand (WD) and specific surface area (SSA) compared to cement. The effect of partial substitution of cement at 20 vol-% with binary and ternary blends of CC and RHA on flowability retention an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…And the water absorption of concrete decreased by 9.7%, and for mortar it decreased by 9.3%. This is in good agreement with the works of a number of authors, in particular with the works [13][14][15][16][17][18][19] devoted to the processes of structure formation of concrete composites using coal dust and the works of the authors [20][21][22][23][24][25][26][27] devoted to the physical and mechanical characteristics of concrete modified with coal dust. Based on the results of XRD analysis of concrete of the control composition, the phases of portlandite, illite, anorite, calcite and quartz were identified.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…And the water absorption of concrete decreased by 9.7%, and for mortar it decreased by 9.3%. This is in good agreement with the works of a number of authors, in particular with the works [13][14][15][16][17][18][19] devoted to the processes of structure formation of concrete composites using coal dust and the works of the authors [20][21][22][23][24][25][26][27] devoted to the physical and mechanical characteristics of concrete modified with coal dust. Based on the results of XRD analysis of concrete of the control composition, the phases of portlandite, illite, anorite, calcite and quartz were identified.…”
Section: Resultssupporting
confidence: 90%
“…It should be noted that, based on the results of the literature review, no studies were found on the use of coal dust with a similar chemical composition as a partial replacement for binders in the technology of cement composites. However, there are a number of studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] where the use of inert mineral additives, namely, clay, metakaolin, electric arc furnace dust, stone dust and finely ground sea shell powders, as a partial replacement for cement allows in rational amounts the improvement of the physical and mechanical characteristics of the composite and at the same time an increase in its environmental friendliness. The optimal percentages for replacing part of the cement with these types of additives varied from 2% to 20%, while improvements in the strength characteristics, water absorption and porosity of experimental cement composites were observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of ternary blended cements is a focus of interest because this combination enhances sustainability [22], workability [23] and mechanical/durability properties [24].…”
Section: Introductionmentioning
confidence: 99%